Design for safety implementation among design professionals in construction: The context of Palestine. (August 2020) - Abueisheh, Qusai; Manu, Patrick; Mahamadu, Abdul-Majeed; Cheung, Clara
Highlights: Design for safety (DfS) implementation by designers in Palestine is investigated. There is high awareness of DfS and positive attitude towards DfS. There is high interest in DfS professional development training. There is low implementation of DfS. Efforts are required to improve DfS implementation. Abstract: Design for safety (DfS), also known as prevention through design, is a prominent means for tackling work-related illnesses and injuries in construction. However, the available DfS studies in construction have paid very limited attention to developing countries. Consequently, there is limited insight into DfS implementation in many developing countries including Palestine. This study therefore investigates DfS implementation among design professionals in the Palestinian construction industry. A questionnaire survey was used to obtain data from design professionals and the data was analysed using inferential statistics (i.e. analysis of variance and t -test) and descriptive statistics. The results revealed that the extent of engagement in DfS practices among the design professionals is very low despite a high awareness and positive attitude towards the concept of DfS. Additionally, while there is a great interest in undertaking DfS training, the designers' participation in training is low. Additionally, awareness of DfS, DfS education and training, professional body affiliation, level of education, years of experience, and size of organisation were found to have limited association with the extent of engagement in DfS practices by the designers. These findings suggest the presence of DfS implementation barriers/challenges, which are undermining the implementation of DfS by the design professionals in Palestine. Collaborative efforts are required by the construction industry stakeholders to improve DfS implementation. Furthermore, the findings mirror the outcomes of similar studies in other developing countries and thus highlight an urgent need for additional studies within developing countries to ascertain the barriers/challenges to DfS implementation in those geographic contexts.